Progress in immunotherapy for brain metastatic melanoma - Zheng, Shicheng; Lin, Zhongqiao; Zhang, Ruibo; Cheng, Zihang; Li, Kaixin; Gu, Chenkai; Chen, Yu; Lin, Jing (Frontiers in Oncology, 2025)
Melanoma is highly aggressive, with brain metastasis being a significant contributor to poor outcomes. Immunotherapy has emerged as a crucial treatment modality for melanoma, particularly for addressing brain metastases. This review explores recent developments in immunotherapy for patients with melanoma brain metastasis, with such treatments encompassing immune checkpoint inhibitors and various immunotherapy combination approaches, such as dual immunotherapy, immunotherapy combined with chemotherapy, immunotherapy combined with targeted drugs, and immunotherapy combined with radiotherapy. This article also discusses existing treatment obstacles and potential future avenues for research and clinical practice.